Penerapan Model Struktural Berhierarki pada Kualitas Layanan Shopee, Motivasi Berbelanja, dan Loyalitas - Damanik, Veni Jean Gabriella; Kencana, I Putu Eka Nila; Gautama, I Putu Winada (Jurnal Matematika, 2023)
Technological advances affect human life, one of which is in the field of trade, namely the existence of an online buying and selling system through e-commerce. The results of research conducted by Ipsos at the end of 2021 on the competition of several e-commerce proved that Shopee is the most popular and widely used e-commerce by the people of Indonesia. This is evident from the quality of Shopee services considered good by consumers so that increase consumer interest and motivation to shop at Shopee and consumer loyalty to Shopee. Therefore, this study aims to determine whether there is an influence of Shopee service quality on shopping motivation and consumer loyalty. To answer the purpose of this study, a hierarchical structural equation modeling (SEM) method was used. Based on the design of the research model and the results of the structural model analysis in the study, it was proven that the service quality construct can explain the shopping motivation construct by 46,3%, while the service quality construct can explain the consumer loyalty construct by 36,5%. Thus, it can be concluded that the quality of service affects shopping motivation and consumer loyalty.